2015
DOI: 10.1007/s10484-015-9312-y
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Coherence Training to Reduce Anxiety in Remitted Schizophrenia, a Pilot Study

Abstract: Health care that addresses the emotional regulation capacity of patients with schizophrenia confronted with daily stress may contribute to a less anxious life. A psycho-physiological training [cardiac coherence training (CCT)] focusing on emotion regulation is known to decrease anxiety for healthy individuals. We performed a pilot cross sectional survey to explore the benefits of CCT for clinically stable patients with schizophrenia. Ten patients were enrolled in the program consisting of twelve weekly 1-h ses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 67 publications
(78 reference statements)
0
10
0
Order By: Relevance
“…Increases yield greater reflex efficiency and hence greater modulation of autonomic activity (Lehrer et al, 2003) and improved emotional regulation, cognitive functioning, and quality of life (Kim et al, 2015). HRV patterns characterized by high-amplitude oscillations (sinusoidal waves) have been associated positively with attention, flexibility of behavior, and control of emotions (Hansen, Johnsen, & Thayer, 2003; McCraty, Atkinson, Tomasino, & Bradley, 2009; Trousselard et al, 2016). Consistent with theoretical contributions on the association of HRV patterns and cognition and behavior (Thayer, Hansen, Saus-Rose, & Johnsen, 2009), a number of studies have found that higher levels of HRV (“enhanced” HRV) have been associated with improved executive functioning (Hansen, Johnsen, Sollers, Stenvik, & Thayer, 2004; Mezzacappa, Kindlon, Saul, & Earls, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Increases yield greater reflex efficiency and hence greater modulation of autonomic activity (Lehrer et al, 2003) and improved emotional regulation, cognitive functioning, and quality of life (Kim et al, 2015). HRV patterns characterized by high-amplitude oscillations (sinusoidal waves) have been associated positively with attention, flexibility of behavior, and control of emotions (Hansen, Johnsen, & Thayer, 2003; McCraty, Atkinson, Tomasino, & Bradley, 2009; Trousselard et al, 2016). Consistent with theoretical contributions on the association of HRV patterns and cognition and behavior (Thayer, Hansen, Saus-Rose, & Johnsen, 2009), a number of studies have found that higher levels of HRV (“enhanced” HRV) have been associated with improved executive functioning (Hansen, Johnsen, Sollers, Stenvik, & Thayer, 2004; Mezzacappa, Kindlon, Saul, & Earls, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The basic goal of BF therapy is to restore normal activity to dysfunctional brain areas. Many publications confirm this dependency, among others works by Trousselard et al [50] and Scheinost et al [51]. These authors believe that regulation of brain waves positively affects the levels of anxiety and uneasiness, symptoms that often accompany schizophrenia.…”
Section: Discussionmentioning
confidence: 83%
“…The high effectiveness of Biofeedback therapy is also emphasised by other authors, who note that regulation of brain waves based on regular training reduces fear, anxiety, and stress levels, that is, those symptoms which are frequently a problem for patients with mental disorders [43][44][45]. It is possible that this relationship is an effect of mental status modulation, and the process of instrumental conditioning is associated with morphological and functional changes in dendrites and neuroplasticity of the brain [46].…”
Section: Discussionmentioning
confidence: 99%